Chapter 22 Ageism and the Rights of Older People (2018)
This chapter critically examines established attempts to counter ageism, highlighting how they have failed to include the so-called fourth age, and might instead contribute to further stigmatization of older people with impairments and care needs. Drawing upon models from disability policies, an equal rights framework will be introduced that could be used to combat discrimination and improve everyday conditions of older people in need of long-term care. In this chapter, the equal rights framework will call into question existing cases of “institutional ageism” whereby older people with impairments are excluded from government programs benefiting younger people with disabilities. Instead of acting as a normative reference group, as the standard that older persons may fail or manage to live up to, it is possible to use the third age as a comparative reference group. We argue that society should make available for older persons with impairments living conditions and lifestyles that are typical for healthy active seniors, that is, for the group of older people that are commonly referred to as constituting the third age. These conditions and activities should then not be regarded as normative, but as typical, and thus possible to refer to when defining social rights.